2015
DOI: 10.3892/ijo.2015.3040
|View full text |Cite
|
Sign up to set email alerts
|

Increased phosphorylation on residue S795 of the retinoblastoma protein in esophageal adenocarcinoma

Abstract: Abstract. Due to its increasing incidence and relatively poor prognosis, esophageal adenocarcinoma (EAC) is becoming a significant health problem. Elucidating the mechanisms underlying EAC development is of great importance to improve upon current conventional treatment strategies. Insight into phosphorylation has proven to be useful for the development of diagnostic and molecular treatment strategies in cancer. A pathway largely dependent on phosphorylation and frequently deregulated in cancer is the cell cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
2
1
Order By: Relevance
“…This finding contributes to the scarce literature on the status of the pRB pathway in esophageal cancers, indicating that pRB hyperphosphorylation is important in esophageal adenocarcinoma tumor progression [31], [34]. In contrast, our analysis of the pRB phosphorylation status on squamous cell carcinoma yielded no consistent results among the different samples.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…This finding contributes to the scarce literature on the status of the pRB pathway in esophageal cancers, indicating that pRB hyperphosphorylation is important in esophageal adenocarcinoma tumor progression [31], [34]. In contrast, our analysis of the pRB phosphorylation status on squamous cell carcinoma yielded no consistent results among the different samples.…”
Section: Discussioncontrasting
confidence: 70%
“…However, the literature on the status of the pRb pathway in esophageal tumors is scarce. A study by Davelaar and colleagues in 2015 showed that adenocarcinoma cell lines and tissue samples have increased pRB phosphorylation at its serine 795 residue compared to normal esophageal tissue samples [31]. This finding suggests that, in esophageal adenocarcinoma, as in colon cancers and glioblastomas, the pRB pathway may be altered by pRB hyperphosphorylation, rather than by the loss of Rb-1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation